Experimental and numerical investigation of a bolt-sleeve device for enhanced ductility of steel connections - Atar, Muhammed; Shaheen, Mohamed A. (Elsevier Science Inc, 2026)
This study investigates a sleeve mechanism as an energy-dissipating and ductility-enhancing solution for bolted steel connections. A comprehensive experimental program was conducted on T-stub specimens incorporating sleeves with varying geometrical parameters, and the results were compared against standard configurations to evaluate improvements in strength and deformation capacity. Finite element (FE) models were developed and validated using the experimental data. The findings confirm the effectiveness of the proposed sleeve device, demonstrating more than a twofold increase in deformation capacity and up to an 80% enhancement in energy dissipation. These outcomes highlight the potential of the sleeve mechanism for improving the seismic resilience and robustness of steel moment connections, while also providing a practical basis for retrofit strategies and future advancements in bolted joint design.
Keywords: Ultimate capacity; Bolted connection; Sleeve fuse system; T-stub connections, Ductility, Failure mode